ChemInform Abstract: An Efficient One‐Pot Protocol for the Conversion of Benzaldehydes into Tetrazole Analogues. Issue 21 (6th May 2016) - Khan, Khalid Mohammed; Fatima, Itrat; Saad, Syed Muhammad; Taha, Muhammad; Voelter, Wolfgang
Abstract: A tandem transformation of benzaldehydes affords 5‐phenyltetrazoles via non‐isolated oxime and nitrile intermediates.